"Sometimes a Bee Can Move an Ox": Biblical Epics and One Man's Quest to Promote Jewish Values in Blacklist-Era Hollywood. Issue 2 (15th May 2018) - Paul, Andrew
Abstract : In the 1950s, the top American Jewish organizations chose a single man, John Stone, to represent their collective interests in Hollywood. Over the course of the decade, Stone's Motion Picture Project sought to prevent antisemitism on film and to inspire the creation of positive Jewish characters. Negotiating the cultural politics of the era, however, resulted in an increasing tendency to favor depictions of biblical Jews over contemporary American ones. In a strange twist, Stone endorsed no film with as much zeal as Ben-Hur, a New Testament celebration of Jesus. By following Stone's tortuous attempts to navigate Cold War controversies, and by casting new light on the phenomenal success of biblical epics in the 1950s, this essay suggests that at the heart of postwar popular culture was a shift toward a particular discourse of liberal humanism.